Reviews of Energy Storage Participating in Auxiliary Services Under Ubiquitous Internet of Things - Hui WANG; Dengxiang LIANG; Xiaojuan HAN (发电技术)
With the gradual deepening reform of the power system and the gradual improvement of the power market trading mechanism, it provides a new opportunity for the development of energy storage technology, and the energy storage technology presents a good trend of diversified development. The establishment of an auxiliary service compensation mechanism has accelerated the penetration of energy storage systems in the auxiliary service field. The auxiliary service market has become one of the main application directions of energy storage technology. The participation mechanism was investigated, the status of energy storage technology in auxiliary services were researched, and the application scenarios and main research directions of energy storage technology in power system auxiliary services were summarized. At the same time, combined with the construction of the ubiquitous power internet of things, the business model of energy storage participating in auxiliary services in China was discussed.